(untitled) (Biological Sciences - PJSIR, 2021)
A field experiment was carried out to test the result of foliar application of micro nutrients on growth, quality and yield of three wheat verities. The trial was performed at Agronomic research area, University of Agriculture Faisalabad. Wheat varieties Jouhar 2016, Ujala 2015 and Gold 2016 were sown. Combination of micro nutrient (Zn 2%, B 0.5%, Fe 1%, Mn 1% and Cu 0.5%) with different amounts (no spray, water spray, 1000 mL/ha, 1250 mL/ha and 1500 mL/ha) was sprayed at booting stage. By results of this study,it is concluded that foliar spray of micro nutrients has significant effect on growth, yield and quality parameters. Statistically highly significant effect of 1250 mL/ha spray of micro nutrients mixture was observed on plant height (105.33 cm), grains/spike (48), grain yield (5336.3 Kg/ha), biological yield (12829 Kg/ha), carbohydrates (63.7%) and protein (11.4%) under V2F4 (Ujala 2015 + 1250 mL/ha micro nutrients).